Peran Camera Person Dalam Produksi Tugas Akhir Karya Aplikatif Dokumenter : Jejak Rasa, Ruang Hidup - Fauzan Syahbilla Rasyid; R. Hiru Muhammad (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The documentary “Jejak Rasa, Ruang Hidup” explores the interconnection between urban spaces and the traces of taste embedded in emotions, memories, and community identity, with Surya Kencana, Bogor, chosen as a representative public space. Through a soft news approach, this work emphasizes narrative strength, atmosphere, and emotional experiences emerging from culinary traditions and intergenerational social interactions. Within the production process, the role of the camera person is crucial in capturing visuals that convey the cultural values and atmosphere of the area. The camera person does not merely operate as a technical image recorder, but also as an active observer, sensitive to moments, rhythms of activity, and human expressions within the public space. The main tasks of a camera person include selecting appropriate angles, compositions, and camera movements to support the documentary’s narrative. The use of varied shots such as wide shots to depict spatial context, medium shots to highlight social interactions, and close-ups to capture emotional expressions serves as a visual strategy to strengthen the connection between urban space and collective identity. Furthermore, the camera person is responsible for maintaining visual continuity to ensure that the footage aligns with the editor’s needs in shaping a reflective and immersive storyline. The final outcome of the documentary demonstrates that collaboration between narrative, visuals, and audio creates a viewing experience that is both factual and emotionally engaging. Thus, the role of the camera person is proven to extend beyond technical operation, functioning as a creative contributor significantly shaping the documentary’s communicative success.